Estudo de extinção de arco secundário no religamento monopolar de linhas de extra-alta tensão - Ricardo de Magalhães Araújo (2019)
This work deals with single-phase auto reclosing in extra high voltage overhead transmission lines. The characteristics, limitations and main requirements for this switching operation are discussed. Among these requirements special attention is given to the extinction of the secondary electric arc, which is extremely important for the success of the switching operation but is difficult to determine. For this, studies and evaluations of electric arc models were carried out with the purpose of verifying their ability to reproduce the real arc behavior and its interaction with the power system. It is also verified if it is possible to determine, using these models, the time required for the extinction of the electric arc in a specific electrical system based on computer simulations. In order to carry out the proposed evaluation, a case study is presented based on a real system. In this study, real cases of single-phase reclosing performed in a 500 kV line of the CEMIG GT were reproduced by simulations with arc and transmission line models using the software Alternative Transients Program (ATP). Voltage and current waveforms calculated at the line terminations under fault conditions present good agreement with measured data, especially for one of the evaluated arc models. This suggests the validity of the employed methodology. However, although they are able to represent the occurrences with sufficient accuracy, the models require parameters that depend on environmental conditions, which are hardly available. Simulations were also carried out considering strategies for mitigating the secondary arc, such as the use of neutral reactor and fast grounding switches, whose efficacy was proved. Finally, from measured and simulated results, the third harmonic of the voltage waveforms were estimated at the line terminal. This parameter, which works as a secondary arc detector, is one of several adaptive single-phase reclosing techniques available in the literature. The results show that this is an efficient arc extinction detector, and that the arc models provide third harmonic voltage levels similar to those of the real arc.